The Mealsfessional's Meals Ready to Eat (MRE) / Nurul Nasriah Mohd Sazli ... [et al.] - Mohd Sazli, Nurul Nasriah; Ungku Suzaini, Ungku Hafiz; Mahiuddin, Nur Ainanisa; Mohd Zaid, Muhammad Syahmi
MREs, or Meals Ready to Eat, are used by military across the world to keep their troops fed and ready to battle. MREs (Military Ready-to-Eat) provide soldiers with a basic source of nutrition and calories. MREs, on the other hand, are now widely used in society. It is necessary to ensure that militaries have timely access to vital nutrients in order to maintain personnel combat-ready. People's eating habits are rapidly altering these days. Fast food is gaining popularity among many individuals, particularly young adults, who prefer it to home-cooked meals. Time-consuming eating may be unimportant for some in this advancing technological era. A portion of the world's population prefers meals that are quick to prepare, taste well, and are not time intensive. However, there are few items that meet the consumer's criteria and standard demands. The Mealsfessional's Meals Ready to Eat is a new product from a new company that has been developed and renovated into a better and handy product. The items were created following a thorough examination and investigation of the materials used as starting points. Current on-the-market items with plastic cutlery, tiny serving portions, and plastic or packaging waste are causing problems for many customers. With edible spork, a mix of spoon and fork, and biodegradable packaging, our brand presents the zero-waste idea. Our target market for this product is tourists and outdoor enthusiasts who want quick and excellent meals throughout their activities. Our product is now relevant to them because of the biodegradable packaging and edible spork, both of which suit their nature-loving viewpoint. To avoid any waste, particularly plastic garbage. We feel our Ready-to-Eat Meals will be a welcome addition to the market